Food Vlogger Reels Content @Makanbarengading on Instagram Social Media in Fostering Interest in Culinary Tourism in Cirebon City - Aviantineke, Vradnya Paramitha; Nurfalah, Farida; Wihayati, Welly (Ridwan Institute, 2025)
Cirebon City, with its diverse culinary and cultural richness, stands as a potential culinary tourism destination due to the uniqueness of its specialties, such as empal gentong, nasi jamblang, and tahu gejrot, which attract both local and foreign tourists. This study explores the influence of food vlogger @makanbarengading’s Instagram Reels content in cultivating culinary tourism interest in Cirebon City. As digital media increasingly shapes consumer behavior—especially among millennials and Gen Z—visual content such as short-form videos has become a powerful tool for destination promotion. Using a qualitative descriptive approach, this research analyzes the thematic elements, visual strategies, and engagement metrics of selected Reels posted by @makanbarengading. The findings indicate that well-curated food content showcasing local Cirebon delicacies, combined with narrative authenticity and visual aesthetics, significantly attracts viewers and encourages culinary exploration. Furthermore, the strategic use of Instagram features such as location tagging, trending audio, and call-to-action captions enhances audience interest and interaction. This study underscores the role of digital influencers as key agents in tourism promotion and provides insights for stakeholders in Cirebon’s tourism and food sectors to optimize their social media strategies.